''Rubbish''. (1st February 2015) - Russell Fraser
Abstract : That's the verdict of an eminent public law barrister and QC on the Government's proposed plan to radically alter the UK's relationship with the European Court of Human Rights. Is she right? Russell Fraser thinks so……